2006
DOI: 10.1111/j.1365-2621.2005.01110.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, microstructural and textural characterisation of gelatinised corn, cassava and yam starch blends

Abstract: The functional properties of mixtures of maize, cassava and yam starches and their relationships with microstructural characteristics were investigated. Experiments were performed following the simplexcentroid design with internal points and restrictions (upper limit) for yam starch proportion. The statistical model used (Scheffe´canonical equation) was a powerful tool to predict the pastes behaviour within the limits of the experimental area. Polynomials with second level interactions were applied to obtain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 26 publications
2
32
0
2
Order By: Relevance
“…When mixed with excessive water (>65 % water content), individual starch tends to gelatinize independently, especially when a large difference in gelatinization temperature exists (at least 6°C) between components, thus avoiding the overlapping of peaks (Waterschoot et al 2015). This was supported by studies observing two endotherms in starch blends of, e.g., canna and potato (Puncha-arnon et al 2008) and cassava and yam (Karam et al 2006). Overlapped endotherms were observed in previous studies on various systems such as potato and maize starch mixture (Obanni and Bemiller 1997) and canna and maize (Puncha-arnon et al 2008).…”
Section: Resultsmentioning
confidence: 86%
“…When mixed with excessive water (>65 % water content), individual starch tends to gelatinize independently, especially when a large difference in gelatinization temperature exists (at least 6°C) between components, thus avoiding the overlapping of peaks (Waterschoot et al 2015). This was supported by studies observing two endotherms in starch blends of, e.g., canna and potato (Puncha-arnon et al 2008) and cassava and yam (Karam et al 2006). Overlapped endotherms were observed in previous studies on various systems such as potato and maize starch mixture (Obanni and Bemiller 1997) and canna and maize (Puncha-arnon et al 2008).…”
Section: Resultsmentioning
confidence: 86%
“…Microscopy studies have suggested that swelling of the starch with the largest granules is reduced in the presence of a starch with smaller granules (Karam, Ferrero, Martino, Zaritzky, & Grossmann, 2006;Lin et al, 2013;Park et al, 2009;Punchaarnon et al, 2008). However, it is still not clear which factors lead to this reduction.…”
Section: Introductionmentioning
confidence: 94%
“…However, it is worthy to note that a high yield of starch does not necessarily mean the starch would have the desired quality for any specific application [51]. Researchers have also shown that blending different native starch sources can give rise to an extensive array of properties, possibly obviating the need for chemical processing and minimising undesired properties of gels of individual starches (e.g., excessive cohesiveness in cassava and exudate in yam and corn) [52,53].…”
Section: Physical Processing Of Cassava For Poultry Feedingmentioning
confidence: 99%